ESG and firm performance: The moderating role of gender diversity - Marheni, Dewi Khornida; Sherry, Sherry; Yulfiswandi, Yulfiswandi (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Disclosure of ESG from companies around the world has experienced a drastic increase, this phenomenon is also accompanied by an increase in socially responsible investment. This study investigates the moderating role of gender diversity in the relationship between the individual dimensions of ESG (environmental disclosure, social disclosure, and governance disclosure) and the company’s performance (Tobin's Q) in IDX companies. The research design is causal-explanatory. Based on the theory of previous findings, hypotheses were developed and tested by applying panel data regression to 42 IDX companies in the period of 2017 to 2021. The results found that disclosure of governance had a significant negative effect on company performance as measured by Tobin's Q. Moderation of gender diversity plays a role in weakening the relationship between governance disclosure with company performance. Several managerial implications are proposed based on this research. Managers may consider other ways to address stakeholder concerns about environmental and social performance. Indonesian policymakers can authorize regulations regarding ESG disclosure requirements to boost firm performance and lead to economic stability.